A Look at Sustainability and Vulnerability in School Reform - Gary Andersen; Linda E Feldstein; Matthew Clay (The Advocate, 2025)
This qualitative study sought stakeholder perspectives on the Kansas Department of Education's "Kansas Can" school redesign initiatives. Interviews with stakeholders revealed both sustainable and vulnerable aspects of the school reforms across cultural, political, and technological dimensions.
Keywords: School Reform; School Redesign